2017
DOI: 10.1016/j.foodchem.2017.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Ser2 from Serratia liquefaciens L53: A new heat stable protease able to destabilize UHT milk during its storage

Abstract: The heat-stable protease Ser2 is secreted by the species Serratia liquefaciens, a psychrotrophic bacteria frequently found in raw milk. To understand the physicochemical modifications of casein micelles induced by Ser2 and to confirm its implication in UHT milk destabilization, the enzyme was purified and added to microfiltered raw milk before UHT treatment. UHT milk destabilization was investigated during 90days of storage. A visual destabilization appeared after 8days of storage with the presence of sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Of the psychrotrophic bacteria found in milk, species from the Pseudomonas genus are the most common and most widely studied in respect to UHT milk stability; however, other genera such as Bacillus (Janstova, Lukasova, Drackova, & Vorlova, ; Machado et al., ) and Serratia (Baglinière et al., ; Bagliniere, Jardin, Gaucheron, de Carvalho, & Vanetti, ; Machado, Baglinière et al., ) species can also produce heat‐stable enzymes. Several studies have attempted to isolate and characterize the specific heat‐stable extracellular proteases secreted by the psychrotrophic bacteria, especially those from the Pseudomonas genus (Bagliniere et al., ; Bagliniere et al., ; Baur et al., ; Dufour et al., ; Mateos et al., ; Mitchell et al., ).…”
Section: Age Gelationmentioning
confidence: 99%
“…Of the psychrotrophic bacteria found in milk, species from the Pseudomonas genus are the most common and most widely studied in respect to UHT milk stability; however, other genera such as Bacillus (Janstova, Lukasova, Drackova, & Vorlova, ; Machado et al., ) and Serratia (Baglinière et al., ; Bagliniere, Jardin, Gaucheron, de Carvalho, & Vanetti, ; Machado, Baglinière et al., ) species can also produce heat‐stable enzymes. Several studies have attempted to isolate and characterize the specific heat‐stable extracellular proteases secreted by the psychrotrophic bacteria, especially those from the Pseudomonas genus (Bagliniere et al., ; Bagliniere et al., ; Baur et al., ; Dufour et al., ; Mateos et al., ; Mitchell et al., ).…”
Section: Age Gelationmentioning
confidence: 99%
“…Rennet coagulation of milk takes place at two steps: rennet causes proteolysis of κ-casein by breaking the Phe 105 -Met 106 peptide bond leading to destabilization of the casein micelle and the following of aggregation results in gel formation (19). Gel formation at normal pH of milk takes place after at least 85 to 90% κ-casein has been hydrolyzed (31). In this paper no gel formation was observed, since rennet activity was controlled by heat treatment, it was concluded that less than 85% of the κ-casein was hydrolyzed.…”
mentioning
confidence: 58%
“…According to the present paper, estimating the heat stability for large and small casein micelles in milk, under the same conditions is variable. This could be as a result of distribution of casein micelles size dispersion which dictates the rate of sedimentation and diffusion (31). These results were comparable with those obtained by Lin et al (2016) who studied the fortification of milk protein content with different dairy protein powders and found that the aggregation behavior of proteinfortified milk samples (125 to 142 nm) is strongly influenced by the degree of mineralisation of the protein powder used in fortification, which affects the partitioning of casein and calcium in the sedimentable and nonsedimentable phases (33).…”
mentioning
confidence: 99%
“…Recent studies have shown that Pseudomonas is not the only psychrotrophic genus frequently encountered in raw milk with the capacity to secrete a heat‐resistant protease. The genus Serratia , especially the species Serratia liquefaciens , is also frequently found as a psychrotrophic contaminant in raw milk (Baglinière, Jardin, Gaucheron, De Carvalho, & Vanetti, ,b; Machado et al., ), and it has been shown to secrete a heat‐resistant spoilage‐inducing metalloprotease of approximately 52 kDa encoded by the Ser2 gene. The protease was therefore named Ser2.…”
Section: Relationship Between Aprx and The Instability Of Uht Milkmentioning
confidence: 99%
“…Baglinière et al. (,b) compared the hydrolysis patterns of caseins by Ser2 and AprX. They found Ser2, like AprX, could hydrolyze β‐, α s ‐, and κ‐caseins in UHT milk, thereby destabilizing casein micelles.…”
Section: Relationship Between Aprx and The Instability Of Uht Milkmentioning
confidence: 99%